Odpowiedź:
a)
5(x - 2) + 6(x² - 3) = 5x - 15 + 6x² - 18 = 6x² + 5x - 33
b)
7(x + 6) + 8(x - 4) - 9(x + 1) = 7x + 42 + 8x - 32 - 9x - 9 =
= 6x + 1
c)
2(x + 3y) - 3(4x - y) + 4(2x - 3y) = 2x + 6y - 12x + 3y + 8x - 12y =
= - 2x - 3y
d)
4(2x - 6y + 9) = 8x - 24y + 36
e)
(- 3a - 2b - 1) * 8 = - 24a - 16b - 8
f)
3(x³ + 2x² - x) = 3x³ + 6x² - 3x
g)
[5(2x - 4y) + 6(- 10x - 15y)] : 10 = (10x - 20y - 60x - 80y) : 10 =
= (- 50x - 100y) : 10 = - 50/10x - 100/10y = - 5x - 10y
h)
5xy(2x + 3y) - 3x(xy - 2y²)= 10x²y + 15xy² - 3x²y + 6xy² =
= 7x²y + 21xy²
i)
2x(x + y) = 2x² + 2xy
j)
(6x² - 5x + 8) * 4x = 24x³ - 20x² + 32x